Diagnostic utility, safety, and cost-effectiveness of emergency department-initiated early scheduled technetium-99m single photon emission computed tomography imaging followed by expedited outpatient cardiac clinic visits in acute chest pain syndromes - Wong, R.C. (2016)
10.1007/s10140-010-0874-y